Eye hEar the visual in music - Shaw-Miller, Simon (Surrey Ashgate, 2013)
Eye hEar The Visual in Music' employs the concept of the visual in proximate relation to music, producing a tension: 'is it not the case that there is a gulf between painting and music, between the visible and the audible? One is full of colour and light yet silent; one is invisible and marvellously noisy.' Such a belief, this book argues, betrays an ideological constraint on music, desiccating it to sound, and art to vision. The starting point of this study is more hybrid (and hydrating): that music is never employed without numerous and complex intersections with the visual. By involving the concept of synaesthesia, the book evokes musics multi-sensory nature, stops it from sounding alone, and offers music as a subject for art historians. Music bleeds into art and visuality, in its graphic depiction in notation, in the theatre of performance, its sights and sites. This book looks at music in its absolute guise as a model for art; at notation and the conductor as the silent visual fulcra around which music circulates; at the music and image of Erik Satie; at the concert hall as white cube; at the symphonic film '2001: A Space Odyssey'; and at the liminality of John Cage and Andy Warhol.Contents: Preface; Introduction; Opening our eyes to hear more clearly: the culture of synaesthesia; Pan and panoptes: music aspires to the condition of art; Scores, Satie and the New York School: mingling image, music and text; White cubes and black monoliths: a fantasia; Outside the frame: liminal sights and sounds in the work of Cage and Warhol; Coda: art, music, seeing sound; Select bibliography; Index.About the Author: Simon Shaw-Miller is the Professor of History of Art at the University of Bristol, UK, and Honorary Associate and Research Fellow of the Royal Academy of Music, London.Reviews: By claiming boldly that music is a subject for art historians, Simon Shaw-Miller has laid down the gauntlet for musicologists in this remarkable book. Rich with references to historical and philosophical discussions on the links between music and visual art, Shaw-Miller has produced a work that is also replete with profound aphorisms and sharp insights into specific case studies. Seminal in its contribution to our understanding of the interlocking relationship between the visual and the musical, this book is no less than a manifesto for future scholarship.Alan Davison, University of New England, Australia